Instilling the Values of Religious Moderation in Preventing Bullying Behavior in Islamic Boarding School-Based Educational Institutions - Ahmad Zubaidi; Atika Huril’in; Hasan Jali (Edukasia Islamika : Jurnal Pendidikan Islam, 2025)
The prevalence of bullying in junior high schools has prompted the need for a values-based character education approach, particularly through the instillation of religious moderation values. This study aims to analyze how religious moderation values ​​can serve as a preventive measure against bullying behavior at Nurul Jadid Junior High School. The study employs a qualitative approach with a field research strategy, implemented through case studies that involve observation, in-depth interviews, and documentation. The results show that activities that integrate moderate values, such as tolerance, empathy, justice, and deliberation, in both religious and social contexts contribute to shaping more inclusive student attitudes and to preventing discriminatory or aggressive behavior towards peers. In addition, teacher involvement, a dialogic learning structure, and a supportive school environment strengthen the value of religious moderation. This approach shows that religious moderation is not merely a normative concept but an educational practice lived in students' daily lives. This study concludes that the systematic and sustainable instillation of religious moderation values has the potential to create a safe and harmonious school climate, making it an effective long-term strategy for preventing bullying at Nurul Jadid Paiton Probolinggo Junior High School.